2005
DOI: 10.1016/j.apcata.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Description of coordinatively unsaturated sites regeneration over MoS2-based HDS catalysts using 35S experiments combined with computer simulations

Abstract: catalysts (ca. 10 kcal.mol -1 ), which suggests that the mechanism on the promoted catalyst differs from that on the un-promoted one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 95 publications
(83 reference statements)
2
17
0
1
Order By: Relevance
“…Several studies have been focused on a deeper description of the catalytic active phases, promoter location, stabilization of sulfur vacancies, or the atomic description of model surface‐molecule interactions . Other studies have reported the adsorption energies of the S‐containing molecules on a catalyst surface and the charge transfer between the organic molecules and the metal active sites .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been focused on a deeper description of the catalytic active phases, promoter location, stabilization of sulfur vacancies, or the atomic description of model surface‐molecule interactions . Other studies have reported the adsorption energies of the S‐containing molecules on a catalyst surface and the charge transfer between the organic molecules and the metal active sites .…”
Section: Introductionmentioning
confidence: 99%
“…12 Low valence sulfur species located on the MoS 2 edges were supposed earlier to be involved in H 2 activation, further research suggested that the presence of some hydrogencontaining species on the surface of unsupported overstoichiometric MoS 2+x , able to hydrogenate olefins in the absence of H 2 . 15 In the Co-Mo-S case, the most stable structure has sulfur vacancies and SH groups on the S dimmers, while a fully hydrogenated structure is found to be almost as stable. Dumeignil and colleagues showed that the CUS formation over MoS 2 is most likely to occur on the metallic edge through the release of an H 2 S molecule.…”
Section: Introductionmentioning
confidence: 88%
“…All of the previously mentioned research concludes that molecular hydrogen adsorption on the Mo-edge of the MoS 2 surface is heterolytic, and some groups even suggest that this is the rate-determining step of the overall reaction. It should be noted that Dumeignil et al 12 The investigation reported here is directed at determining the optimum adsorbed sulfur surface coverage (% S ) at typical SOFC operating conditions, that is, the higher temperature of 800°C and the lower H 2 S/H 2 anode fuel pressure ratio of 10 -5 . A further objective in our research is to study methods to remove excess adsorbed sulfur from the MoS 2 surface via the formation of S 2 (g) and SO 2 (g), to avoid SOFC anode degradation.…”
Section: Introductionmentioning
confidence: 98%